2010
DOI: 10.1111/j.1750-3841.2010.01912.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Weight and Structure of Water Soluble (1→3), (1→4)‐β‐Glucans Affect Pasting Properties of Oat Flours

Abstract: Seven experimental oat lines with high (5.9% to 7.2%), medium (5.3% to 5.5%), and low (4.4%) β-glucan concentrations were evaluated for the effects of β-glucan molecular weight (MW) and structure on viscosities of oat-flour slurries. The MW of β-glucans was determined by size-exclusion high-performance liquid chromatography. The structural features of β-glucans were measured by using fluorophore-assisted capillary-electrophoresis after complete hydrolysis with lichenase. The oat-slurry viscosities were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Several studies 101 103 identified that oat β-glucan content falls roughly within 2.5-8.3 of dry grain. In addition, β-glucan polydispersity 104 such as polymer molar masses distribution and polymerization degrees were interesting because the higher-molecular-weight components were highlighted to be biologically beneficial and effective. Report of Lazaridou and Biliaderis 105 proved the significance of the molecular weight of β-glucan polydispersity covering the range of 65-3100 kDa.…”
Section: Carbohydrates: Ber and Starchmentioning
confidence: 99%
“…Several studies 101 103 identified that oat β-glucan content falls roughly within 2.5-8.3 of dry grain. In addition, β-glucan polydispersity 104 such as polymer molar masses distribution and polymerization degrees were interesting because the higher-molecular-weight components were highlighted to be biologically beneficial and effective. Report of Lazaridou and Biliaderis 105 proved the significance of the molecular weight of β-glucan polydispersity covering the range of 65-3100 kDa.…”
Section: Carbohydrates: Ber and Starchmentioning
confidence: 99%
“…The starch-pasting profile of barley products depends on many factors, including cultivar and the amylose/amylopectin ratio (Yanagisawa et al 2006;Gujral et al 2013;Li et al 2014). Additionally, BG largely contributes to the viscosity and needs to be accounted for when analyzing wholegrain barley flour (Liu and White 2011). Typically, viscosity reduction in the starch-pasting profile of cereal grain products is attributed to partial starch gelatinization, which can occur during heat treatment.…”
mentioning
confidence: 99%
“…The RVA has been employed for standard methods in cereal applications, including a method to measure pasting properties of oat flours (AACCI 2010). It was also used to study the effects of β-glucan molecular weight and structure on viscosities of oat flour slurries under different enzyme treatments (Liu and White 2011).…”
mentioning
confidence: 99%